Bridging values: Finding a balance between privacy and control. The case of Corona apps in Belgium and the Netherlands. (7th February 2022) - van Brakel, Rosamunde; Kudina, Olya; Fonio, Chiara; Boersma, Kees
Abstract: This paper focuses on two examples of the introduction and use of COVID‐19 contact tracing apps in The Netherlands (CoronaMelder) and Belgium (Coronalert). It aims to offer a critical, sociotechnical perspective on tracing apps to understand how social, technical, and institutional dimensions form the ingredients for increasing surveillance. While it is still too early to gauge the implications of surveillance‐related initiatives in the fight against COVID‐19, the "technology theatre" put in place worldwide has already shown that very little can be done to prevent the deployment of technologies, even if their effectiveness is yet to be determined. The context‐specific perspective outlined here offers insights into the interests of many different actors involved in the technology theatre, for instance, the corporate interest in sociotechnical frameworks (both apps rely on the Google/Apple exposure notifications application programming interface). At the same time, our approach seeks to go beyond dystopian narratives that do not consider important sociocultural dimensions, such as choices made during app development and implementation to mitigate potential negative impacts on privacy.